Study on Design Textures on Large Format 3D Modals: A Novel Approach for Creating Dynamic 3D Textures (Journal of Advances and Scholarly Researches in Allied Education, 2019)
To create a bright 3D solid texture, a simple 2D texture pattern, an effective model-independent 3D texture synthesis algorithm is presented based on texture turbulence and texture turbulence. Due to the 2D texture pattern of some increasing material, our technique can produce a 3D volumetric cube anisotropic texture to simulate 3D material development. An effective tiling system is designed to save computer and storage costs. Target objects are immersed directly in the synthesised volume of 3D textures in order to generate creative, sculptural models that can be visualised interactively. Compared to other solid texture methods, our method is conceptually intuitive, quick computational and efficient storage. Our approach is able to seamlessly decorate 3D point rendering systems, contrary to conventional 2D texture maps on polygonal surfaces. Our combination of texture turbulence and texture-growing techniques also offers an attractive way of synthesising, tiling and creating natural 2D textures or simply interesting movement textures.